Comparison between conventional solvothermal and aqueous solution-based production of UiO-66-NH2: Life cycle assessment, techno-economic assessment, and implications for CO2 capture and storage. Issue 2 (April 2021) - Luo, Hongxi; Cheng, Fangwei; Huelsenbeck, Luke; Smith, Natalie
Abstract: Metal-organic frameworks (MOFs) are a new class of materials that has shown great potential in catalysis, sensing, separations, and carbon capture and storage. Conventionally, MOFs are synthesized at lab-scale using organic solvent-based systems, leading to high environmental burdens and high operating costs, which ultimately hinders the large-scale production and application of MOFs. Aqueous synthesis of MOFs overcomes such difficulty by eliminating the organic solvent, which makes it an environmental-friendlier and economically-favorable alternative to the current production method. However, further quantitative analysis is required to compare the environmental and economic performances of the two methods. Here, we used life cycle assessment (LCA) coupled with techno-economic analysis (TEA) to evaluate the environmental and economic performances of different UiO-66-NH2 production methods. When the solvothermal method was replaced by the aqueous solution-based method, the LCA and TEA results suggest the environmental burdens and cost of UiO-66-NH2 production were reduced by up to 91% and 84%, respectively. By using aqueous solution-based method, the cradle to gate carbon footprint, and production cost of UiO-66-NH2 were estimated to be 43 kg CO2 eq/kg, and 15.8/kg, respectively. We further applied our LCA results to reassess the role of UiO-66-NH2 in carbon capture and storage (CCS) and compare its environmental performance with current benchmark (amine-based solvent). Our results show that electricity produced from UiO-66-NH2 CCS system could potentially have better environmental performance (lower Global Warming Potential (GWP)) than that of the amine-based CCS system if the sorbent loss is less than 0.0017 tonne/tonne CO2 captured. This work is the first comprehensive LCA-TEA study that quantifies the substantial environmental and economic benefits of using the aqueous solution-based systems to produce UiO-66-NH2, and the analysis in this work is intended to be a starting point for further systematic studies on the full life-cycle impacts of MOFs. Graphical Abstract: ga1 Highlights: Life cycle assessment and techno-economic assessment were performed on the UiO-66-NH2 production for the first time. Significant environmental and economic benefits of aqueous solution-based UiO-66-NH2 production were quantified. Amine-based CCS and UiO-66-NH2 (aqueous)-based CCS were compared on conventional coal fired power plant. The UiO-66-NH2 (aqueous)-based CCS may have better performance if the sorbent loss is less than 0.0017 t/t CO2.